Improved adsorption performance of nanostructured composite by ultrasonic wave: Optimization through response surface methodology, isotherm and kinetic studies - Dastkhoon, M.; Ghaedi, M.; Asfaram, A.; Goudarzi, A.; Mohammadi, S.; Wang, Shaobin (Elsevier, 2017)
© 2016 Elsevier B.V.In this work, ultrasound-assisted adsorption of an anionic dye, sunset yellow (SY) and cationic dyes, malachite green (MG), methylene blue (MB) and their ternary dye solutions onto Cu@ Mn-ZnS-NPs-AC from water aqueous was optimized by response surface methodology (RSM) using the central composite design (CCD). The adsorbent was characterized using Field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), Energy-dispersive X-ray spectroscopy (EDX) and EDX mapping images. The effects of various parameters such as pH, sonication time, adsorbent mass and initial concentrations of SY, MG and MB were examined. A total 33 experiments were conducted to establish a quadratic model. Cu@ Mn-ZnS-NPs-AC has the maximum adsorption efficiency (>99.5%) when the pH, sonication time, adsorbent mass and initial concentrations of SY, MG and MB were optimally set as 6.0, 5 min, 0.02 g, 9, 12 and 12 mg L-1, respectively. Sonication time has a statistically significant effect on the selected responses. Langmuir isotherm model was found to be best fitted to adsorption and adsorption capacities were 67.5 mg g-1 for SY, 74.6 mg g-1 for MG and 72.9 mg g-1 for MB. Four kinetic models (pseudo-first order, pseudo-second order, Weber–Morris intraparticle diffusion rate and Elovich) were tested to correlate the experimental data and the sorption was fitted well with the pseudo-second order kinetic model.